Psikoedukasi Pendidikan Seksual dengan Mengajarkan Batasan Privasi Tubuh sebagai Upaya Pencegahan Kekerasan Seksual pada Siswa SD Pertiwi Makassar - Eka Sufartianinsih Jafar; Ruhana Ruhana; Andi Zulfa Afiva; Andi Yahdini Firsyah Nadhirah; Anggun Mutiara (Universitas Negeri Makassar, 2024)
This study aims to evaluate the effectiveness of a psychoeducation program that uses posters to teach body privacy boundaries to students at SD Pertiwi Makassar. The psychoeducation approach included direct explanations of the poster content, small group discussions, and role-playing sessions. Informative and interactive posters were displayed in classrooms and on school bulletin boards as ongoing visual reminders.Qualitative data were gathered through observations and interviews with the students. Results indicated a significant improvement in the students’ knowledge and skills related to body privacy boundaries and self-protection strategies against sexual abuse after participating in the program. Students demonstrated the ability to identify private body parts, understood who is allowed to touch them, and showed an enhanced capacity to refuse inappropriate touches and report incidents. The posters, featuring engaging illustrations and simple language, served as effective visual aids. This study underscores the importance of integrating sex education into the elementary school curriculum in Indonesia, utilizing effective psychoeducation methods such as poster media.